Phylogeographical Analyses and Antibiotic Resistance Genes of Acinetobacter johnsonii Highlight Its Clinical Relevance - Santiago Castillo-Ramírez (American Society for Microbiology, 2020)
ABSTRACT Acinetobacter johnsonii has been severely understudied and its population structure and the presence of antibiotic resistance genes (ARGs) are very much uncertain. Our phylogeographical analysis shows that intercontinental transmission has occurred frequently and that different lineages are circulating within single countries; notably, clinical and nonclinical strains are not well differentiated from one another. Importantly, in this species recombination is a significant source of single nucleotide polymorphisms. Furthermore, our results show this species could be an important reservoir of ARGs since it has a significant amount of ARGs, and many of them show signals of horizontal gene transfer. Thus, this study clearly points out the clinical importance of A. johnsonii and the urgent need to better appreciate its genomic diversity.